Dynamic Modelling of a Double‐Pendulum Gantry Crane System Incorporating Payload - Raja Mohd Taufika, Raja Ismail; Mohd Anwar, Zawawi; Mohd Syakirin, Ramli (American Institute of Physics, 2011)
This paper presents dynamic modelling of a double-pendulum gantry crane system based on closed-form equations of motion. A dynamic model of the system incorporating payload is developed and the effects of payload on the response of the system are discussed. Extensive results that validate the theoretical derivation are presented in the time and frequency domains.